The protective role of melatonin in cadmium-induced proliferation of ovarian cancer cells - Negar Ataei; Mahmoud Aghaei; Mojtaba Panjehpour (Wolters Kluwer Medknow Publications, 2018)
Cadmium (Cd), a ubiquitous environmental and occupational pollutant, acts as a metalloestrogen to induce cell proliferation. It is suggested that Cd may also contribute to the development of estrogen-related cancers like ovarian cancer which is the most lethal cancer in women. Furthermore, it was shown that melatonin has antiproliferative effect on estradiol (E2)-induced proliferation. The aim of the present study was to evaluate whether melatonin inhibits Cd-induced proliferation in ovarian cancer cell lines and also whether Cd and melatonin can modulate estrogen receptor α (ERα) expression. OVCAR3 and SKOV3 human ovarian cancer cell lines were treated with CdCl2 (1-100 nM) and melatonin (1 μM) for 48 h. Cell proliferation evaluation was carried out by bromodeoxyuridine (BrdU) incorporation assay. ERα expression was detected by western blotting method 24 h after cell treatment. The results were demonstrated that Cd increased proliferation of ovarian cancer cell lines in a dose dependent manner. Melatonin inhibited Cd-induced proliferation of OVCAR3 and SKOV3 cell lines. Moreover, CdCl2 significantly increased ERα expression in both OVCAR3 and SKOV3 cell lines compared to control. Melatonin significantly inhibited Cd inducing effect on ERα expression of OVCAR3 and SKOV3 cell. In conclusion, due to the proliferative effect on ovarian cancer cell lines, Cd could play an important role in the etiology of ovarian cancer by inducing cells ERα expression. Furthermore, melatonin has the protective role on Cd-induced cell proliferation by inhibition of ERα expression.